1978
DOI: 10.1017/s0025315400028137
|View full text |Cite
|
Sign up to set email alerts
|

Ciliated Sensory Cells in Amphioxus (Branchiostoma)

Abstract: Various workers during the past century have figured sensory cells bearing cilia amongst the ordinary non-ciliated epidermal cells of the body surface. Similar sensory cells were also found on the buccal cirrhi, and on the velar tentacles at the entry to the atrium. This earlier work at the light microscope level was summarized by Franz (1923) in his excellent review. More recently Schulte & Riehl (1977) have re-examined the innervation of the oral region and buccal cirrhi at the ultrastructural level, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 3 publications
0
38
0
Order By: Relevance
“…The presence of ciliated cells in the epidermis and atrial cavity of amphioxus has been described previously (Bone, 1960b;Bone and Best, 1978;Baatrup, 1981), although they have been interpreted in very different ways. In the atrial region the ciliated cells lack an axon and are contacted at their basal pole by a nerve fiber (Bone and Best, 1978), whereas those of the rostral epidermis bear an axon-like process (Baatrup, 1981). Our immunocytochemical results confirm that ciliated cells of the rostral epidermis have an axon, as suggested by Baatrup (1981), and indicate that many of them are GABA-ir and that their distribution is similar at the two ends of the body.…”
Section: Peripheral Nervous Systemmentioning
confidence: 79%
See 2 more Smart Citations
“…The presence of ciliated cells in the epidermis and atrial cavity of amphioxus has been described previously (Bone, 1960b;Bone and Best, 1978;Baatrup, 1981), although they have been interpreted in very different ways. In the atrial region the ciliated cells lack an axon and are contacted at their basal pole by a nerve fiber (Bone and Best, 1978), whereas those of the rostral epidermis bear an axon-like process (Baatrup, 1981). Our immunocytochemical results confirm that ciliated cells of the rostral epidermis have an axon, as suggested by Baatrup (1981), and indicate that many of them are GABA-ir and that their distribution is similar at the two ends of the body.…”
Section: Peripheral Nervous Systemmentioning
confidence: 79%
“…Our immunocytochemical results confirm that ciliated cells of the rostral epidermis have an axon, as suggested by Baatrup (1981), and indicate that many of them are GABA-ir and that their distribution is similar at the two ends of the body. It has been suggested that ciliated cells are either mechanoreceptors (Bone and Best, 1978) or chemoreceptors (Schulte and Riehl, 1977;Baatrup, 1981). Since some amphioxus apical receptors are GABAergic, they might inhibit locomotion.…”
Section: Peripheral Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the sensory cells of the peripheral nervous system of amphioxus have been studied extensively by microscopy (Frantz, 1923;Schulte and Riehl, 1977;Bone and Best, 1978;Baatrup, 1981Baatrup, , 1982Lacalli and Hou, 1999;, immunostaining (Yasui et al, 1998;Kaji et al, 2001), cell labeling and axon tracing by DiI (Holland and Yu, 2002), and gene expression Mazet et al, 2004), it is not known conclusively whether they are mechanosensory or chemosensory cells.…”
Section: Introductionmentioning
confidence: 99%
“…In the cephalochordate Amphioxus, considered to be the closest living relative of vertebrates, different sensory cells, type I cells and type II cells, are found scattered in the rostral epithelium. Type I cells are primary sensory cells, while type II cells are secondary sensory cells, with synaptic terminals borne out on short extensions of the cell body (Bone and Best, 1978;Lacalli and Hou, 1999;Holland and Holland 2001;Holland and Yu, 2002). For both types of cells, neither their embryological origin nor their functional properties are known, although they are generally assumed to be either mechano-or chemoreceptors on the basis of their morphology.…”
mentioning
confidence: 99%